Association of category of cattle exposure with tuberculosis knowledge among dairy workers in Bailey County, Texas - Rodriguez, Anabel (J Agromedicine, 2020)
OBJECTIVE: To determine the knowledge of TB among dairy workers in Bailey County, Texas. METHODS: A cross-sectional study design was used to collect 225 survey responses concerning knowledge of TB among dairy workers on ten dairy farms in Bailey County, Texas. iPad tablets were used to log responses to 15 demographic questions and 17-item TB knowledge quiz measured by: (1) TB characteristics, (2) TB transmission, (3) TB symptoms, (4) TB diagnosis, (5) TB treatment, and (6) bovine TB. A proxy for exposure, dairy workers were classified into categories of cattle exposure—high, medium, and low. RESULTS: Relative to the medium/low group, workers in the high group tended to be younger (32.6 (SD 11.0)), Guatemalan (52.6%), K’iche’ speaking (37.8%), males (89.1%) with less years living in the U.S. (10.8 (SD 12.5)) and lower levels of formal education completed (59.6% with no formal/elementary level). Overall, the average score was 7.1 (SD 4.9) out of 17 (41.8% out of 100.0%). Relative to one another, the medium/low group (8.0 (SD 4.6) out of 17) scored better than high group (6.7 (SD 5.1) out of 17). No significant associations were found between category of exposure and TB knowledge score. CONCLUSION: Deficiencies in TB knowledge were identified at all categories of exposure. TB training on dairy farms should include all measured tested in this study and should be administered to all workers regardless of category of exposure.